Evaluation of pharmaceutical industry-led access programmes: a standardised framework. Issue 4 (2nd August 2019) - Rockers, Peter C; Laing, Richard O; Scott, Nancy; Ashigbie, Paul; Lucca, Erin H; Umeh, Chukwuemeka Anthony; Wirtz, Veronika J
Abstract : Pharmaceutical industry-led access programmes are increasing in number and scope worldwide. We present a new standardised framework for evaluation of these programmes that includes three components: a taxonomy of 11 access programme strategies; a series of logic models, one for each strategy and a set of measurement indicators. The logic models describe pathways of potential programme impact. Concepts relevant across a broad range of strategies were prioritised for inclusion in logic models to ensure consistency and to facilitate synthesis and learning across programmes. Each concept has at least one corresponding measurement indicator with metadata that includes the definition, details on how it should be measured and recommended data sources. The framework establishes a shared language for the collection and reporting of meaningful industry-led access programme information. Broad adoption by programme developers and implementing partners in the for-profit sector and beyond could facilitate shared learning on effective strategies and best practices.